Influence of land-use systems on hydraulic properties of soils in Yenagoa and Amassoma, Bayelsa State, Nigeria - Agbai, W.P.; Kosuowei, M.T. (International Journal of Environment, 2022)
This research aimed to determine the effect of different land-use systems on the matric potential, and hydraulic conductivity of the soils of Yenagoa and Amassoma communities. Soil samples were collected from four respective land-use types namely: Fallow land, Oil Palm Plantation, Plantain Plantation, and Virgin land. A total of 12 samples were bulked from three replicates at each land use type and were collected at depths of 0-15cm, 15-30cm, and 30-45cm respectively. The samples were taken to the laboratory to analyze their physical, chemical, and hydrological properties. The result showed that the different land use had a significant effect (P